INTERPRETASI STRUKTUR BAWAH PERMUKAAN DAERAH MANIFESTASI PANASBUMI GEDONG SONGO GUNUNG UNGARAN MENGGUNAKAN METODE MAGNETIK - Harri Yudianto; Agus Setyawan (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Interpretation of subsurface structure has done in Gedong Songo geothermal manifestation of Ungaran volcano using magnetic method. Interpretation of subsurface structure showed in two dimensions. The quantitative interpretation result show that, Gedong Songo is compose of 4 main layers. The first layer is sedimentary which consists of breccia, sandstone, pyroclastic deposits, alluvium, and top soil, it have a susceptibility value about 7.0x10-5 cgs emu, the second layer is an alteration of andesite lava, it has a susceptibility value about -1.0x10-2 cgs emu. Third layer is composed of hornblende-augite andesite, it has a susceptibility value about 1.34x10‑2 cgs emu, and the fourth layer is composed of andesite rock, it has susceptibility value about 1.35x10-2 cgs emu. Keywords : Magnetic, susceptibility, geothermal, Gedong Songo